Self Regulated Learning dan Kejenuhan Belajar pada Siswa Kelas XII SMAN 2 Berau : Kurnia Apriyanti, Ahmad Razak, Nur Akmal - Apriyanti, Kurnia; Razak, Ahmad; Akmal, Nur (Fakultas Psikologi Universitas Bhayangkara Jakarta Raya, 2023)
This study aims to determine the relationship between Self Regulated Learning and Learning Saturation in Class XII Students of SMAN 2 Berau. This study used a 142 students taken from the population of class XII students at SMAN 2 Berau using simple random sampling technique. The measuring instrument used uses a scale that is relevant to the two variables to be measured. The results of the hypothesis test showed that the correlation coefficient (r) was = -0.359 with a significant level of p = 0.000. The value obtained indicates that the Ho hypothesis is rejected, and the Ha hypothesis is accepted. The results of this hypothesis test show that there is a significant negative relationship between selfregulated learning and learning saturation in Class XII Students of SMAN 2 Berau. This correlation coefficient shows the closeness of the relationship at a weak level. The implication of this research is that it is hoped that students will be able to fight self-saturation in facing the learning process and be able to understand self-management and self-control in learning well.